When Women Are the Bosses: Linguistic Strategies in Managing Problematic Discourses - Ernanda Ernanda; Delita Sartika (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
The exercise of power in leadership may involve conflicts, especially in precarious situations. Politeness strategies come into practice to cushion the aftermath of face-threatening acts that presumably trigger tension. This study aims to shed light on female leaders' linguistic strategies in managing problematic discourses involving older male subordinates in the Indonesian university context. The naturalistic data was obtained from recorded meetings. The study results depict that the female leader employs both direct and indirect strategies in handling problematic issues, especially when the female leader has to face up to senior subordinates. She adopts direct strategies to convey important messages that have to be obeyed by the employees. On the other hand, she adheres to the cultural norms that oblige younger people to show respect to older people by using indirect strategies. The politeness strategies employed in her utterances show how culture shapes communication approaches. In general, a female leader has to have a range of sophisticated linguistic competence in a high-rank managerial position.